2014
DOI: 10.18632/oncotarget.1821
|View full text |Cite
|
Sign up to set email alerts
|

The role of DNA damage and repair in decitabine-mediated apoptosis in multiple myeloma

Abstract: DNA methyltransferase inhibitors (DNMTi) and histone deacetylase inhibitors (HDACi) are under investigation for the treatment of cancer, including the plasma cell malignancy multiple myeloma (MM). Evidence exists that DNA damage and repair contribute to the cytotoxicity mediated by the DNMTi decitabine. Here, we investigated the DNA damage response (DDR) induced by decitabine in MM using 4 human MM cell lines and the murine 5T33MM model. In addition, we explored how the HDACi JNJ-26481585 affects this DDR. Dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 69 publications
3
50
0
Order By: Relevance
“…Targeting DNA methylation in MM Dec works by inhibiting DNMTs and promoting DNA hypomethylation (35). Previous studies have found that relapsed MM cases had much higher amounts of global DNA methylation compared to monoclonal gammopathy of undetermined significance and newly diagnosed MM cases (36).…”
Section: Clinical Relevance and Disease Specificity Of Qpop Drug Combmentioning
confidence: 99%
“…Targeting DNA methylation in MM Dec works by inhibiting DNMTs and promoting DNA hypomethylation (35). Previous studies have found that relapsed MM cases had much higher amounts of global DNA methylation compared to monoclonal gammopathy of undetermined significance and newly diagnosed MM cases (36).…”
Section: Clinical Relevance and Disease Specificity Of Qpop Drug Combmentioning
confidence: 99%
“…DNA methyltransferase inhibitors (DNMTi), eg, azacitidine and decitabine, have been reported to have anti‐MM effects by inducing cell cycle arrest and impacting the growth of resistant MM cell lines and primary patient‐derived MM cells . Maes and colleagues used a combination of the DNMTi decitabine and the HDACi quisinostat in the in vivo syngeneic 5T33MM mouse model to test the antitumor activity of these epigenetic modulating agents.…”
Section: Epigenetic Targeting As Treatment Of Mmbdmentioning
confidence: 99%
“…These observations are consistent with previous work on the effects of 5azadC showing that only a few hours exposure caused single and double strand breaks, together with decondensation of genetically inactive chromatin (25). 5azadC is a robust inducer of γ-H2AX, an early marker of DSB, activation of DNA repair proteins, and DNA fragmentation (7, 26, 27). Interestingly, the reduction of DNMT1 caused by 5azadC also impairs the cell’s capacity to respond to damage, as DNMT1 is required to co-localise with γ-H2AX at sites of damage.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies to determine the degree of cytotoxicity and DNA damage caused by 5azadC have measured the extent to which H2AX, a key ‘first responder’ in a DNA breakage damage response, is phosphorylated to generate γH2AX (7). While informative, this method is specific to DNA breaks and does not capture the different forms of chromosomal instability induced by hypomethylation and DNA replication stress.…”
Section: Introductionmentioning
confidence: 99%